Electoral Rules and New Parties: Evidence from a Quasi‐experimental Design - Lago, Ignacio (Frontiers in Political Science, 2021)
Electoral rules are a crucial institutional factor shaping the entry and success of new parties. However, testing how they affect voting behavior is problematic when using observational data in cross-national studies. As district magnitude is usually correlated with politically salient features affecting the likelihood of voting for new (and small) parties, the latent support of small parties differs across electoral systems. Using a quasi-experimental design in Spain focused on the district viability of a new party, Vox, in two elections held within 196 days, I provide a more robust estimate of the impact of electoral systems on the success of new parties. Strong evidence that the electoral system makes a difference for new parties has been identified: strategic considerations found in the districts where Vox was not successful prevented a significant number of voters from supporting the party.